2023
DOI: 10.1002/art.42502
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Rheumatoid Arthritis and Osteoporosis in Japanese Populations: A Mendelian Randomization Study

Abstract: Objective The positive association between rheumatoid arthritis (RA) and osteoporosis has been reported in previous observational studies, but the causal relationship remains unclear. This study was undertaken to investigate whether RA was causally associated with osteoporosis in Japanese populations using Mendelian randomization (MR) analyses. Methods Publicly available summarized data from genome‐wide association studies (GWAS) on RA (4,199 cases and 208,254 controls) and osteoporosis (7,788 cases and 204,66… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
(120 reference statements)
0
5
0
Order By: Relevance
“…Similar findings were also observed by Song et al (34), which included European and Asian populations but failed to provide evidence for causation. Conversely, Deng et al (35) demonstrated positive support for a causal relationship between RA and osteoporosis specifically within the Japanese population.…”
Section: Discussionmentioning
confidence: 98%
“…Similar findings were also observed by Song et al (34), which included European and Asian populations but failed to provide evidence for causation. Conversely, Deng et al (35) demonstrated positive support for a causal relationship between RA and osteoporosis specifically within the Japanese population.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, we assessed the causal relationship between RA and miscarriage as well as IUGR by 5 MR methods including inverse variance weighted (IVW) method, MR-Egger, Weighted median (WM), Simple mode, and Weighted mode. [ 18 ] Among these 5 MR methods, IVW is the most dominant MR analysis method, which can effectively assess the causal relationship. However, IVW has some limitations, so we used MR-Egger regression to compensate for the shortcomings of IVW in terms of the instability of multiplicity and to make the causality more stable.…”
Section: Methodsmentioning
confidence: 99%
“…[ 16 ] Therefore, it is a novel method of evaluating causality. [ 17 ] Many scholars have used MR to study the relationship between RA and a variety of diseases such as osteoporosis, [ 15 , 18 ] inflammatory bowel disease [ 19 ] and cancers, [ 20 ] but there is a gap in research on the relationship between RA and adverse pregnancy histories such as miscarriage and IUGR. In this study, for the first time, MR was used to investigate the causal relationship between RA and miscarriage and IUGR.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] Rheumatoid arthritis is closely associated with many diseases. Some Mendelian randomization studies suggest a causal relationship between RA and osteoporosis, [ 10 ] another subset of studies showed that RA is not causally related to osteoporosis, and that osteoporosis in RA patients may be associated with side effects of antirheumatic therapy and reduced physical activity. [ 11 ] Previous studies have found the positive effects of rheumatoid arthritis on inflammatory bowel disease.…”
Section: Introductionmentioning
confidence: 99%